1991
DOI: 10.1515/cclm.1991.29.12.787
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment and Evaluation of Luminescent-Labelled Immunometric Assays for Prostate-Speciflc Antigen-α1-Antichymotrypsin Complexes in Serum

Abstract: Summary:Prostate-specific antigen is found in the prostate in two forms, one with a low (30 000) and one with a high (100000) relative molecular mass. The latter has recently been found to be a complex of prostatespecific antigen with aj-antichymotrypsin.Immunoluminometric assays were designed for the prostate-specific antigen-ocj-antichymotrypsin complex äs well äs for (Xi-antichymotrypsin, the former being compared with a commercially available radioimmunoassay for prostate-specific antigen (ProsChek RIA -Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
2
14
1
2
Order By: Relevance
“…was also stable for at least 5 days at 4°C, 2 months at -20°C and 2 years at -80°C. Using an assay for measuring PSA complexed to cti ACT, we comfirmed previous data [6][7][8][9][10] showing that PSA complexed to a [ACT is the major form of PSA in circulation in prostate cancer and BPH patients, account ing for 91 and 73% of the total PSA immunoreactivity, respectively [11]. We also showed that the use of a totalto-complexed PSA ratio of 0.8 as a cut-off point increased the specificity from 38 to 79% without decreasing the sen sitivity (82%) in patients with prostate cancer with a total PSA concentration <15 ng/ml [11], These results agree with others previously reported [9,12], and suggest that the use of complexed-to-total PSA ratio may help urolo gists to identify patients with organ-confined prostate cancer.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…was also stable for at least 5 days at 4°C, 2 months at -20°C and 2 years at -80°C. Using an assay for measuring PSA complexed to cti ACT, we comfirmed previous data [6][7][8][9][10] showing that PSA complexed to a [ACT is the major form of PSA in circulation in prostate cancer and BPH patients, account ing for 91 and 73% of the total PSA immunoreactivity, respectively [11]. We also showed that the use of a totalto-complexed PSA ratio of 0.8 as a cut-off point increased the specificity from 38 to 79% without decreasing the sen sitivity (82%) in patients with prostate cancer with a total PSA concentration <15 ng/ml [11], These results agree with others previously reported [9,12], and suggest that the use of complexed-to-total PSA ratio may help urolo gists to identify patients with organ-confined prostate cancer.…”
Section: Methodssupporting
confidence: 85%
“…Several groups have therefore studied this problem, and their results show that calculation of the free PSA/total PSA ratio or complexed PSA/total PSA ratio instead total PSA alone provides a better discrimination between be nign prostate hyperplasia and prostate cancer [7][8][9][10][11], Measuring PSA:aiACT complex instead of free PSA has a potential advantage in test samples with low total PSA levels in which only a minimal fraction of PSA is in the free form and most of it is in the form of PSAxxi ACT complex. For example, a plasma sample with a total PSA level of 2 ng/ml where 10% of this PSA in the free form will have only 0.2 ng/ml of free PSA but 1.8 ng/ml of PSA total PSA ratio of 0.80 as a cut-off to exclude prostate can cer, we would have avoided 39 of the 40 biopsies that did not demonstrate cancer in the group of patients with PSA >4 ng/ml and normal DRE and TRUS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There fore, the total PSA measured by available immunoassays consists of the sum of free PSA and the PSA complexed to cii-ACT (PSA:ai-ACT), the latter representing the major portion. Several groups have developed assays to evaluate PSA complexed to arACT and have investigated its use fulness in discriminating between BPH and prostate can cer patients [9,10,12,13]. Stenman et al [9] and Christensson et al [12] found that PSA:ai-ACT is the predomi nant form of PSA in serum from patients with prostate cancer and suggested that calculation of the free/total PSA ratio provides a better discrimination between BPH and prostate cancer.…”
Section: Proteins and Antibodiesmentioning
confidence: 99%
“…The release of active PSA in intercellular fluids or blood plasma would be expected to result in rapid inacti vation of the enzymatic activity by extracellular inhibi tors [6,7], In fact, it has been reported that in prostate cancer patients, free noncomplexed PSA is a minor frac tion in serum [8] and that PSA in blood is bound to a2-macroglobulin (a2-M) and ai-antichymotrypsin (cl-ACT) [8][9][10], but not to protein C inhibitor (PCI) [11], Both the free form and the ai-ACT-bound form are detectable by current PSA immunoassays, but the efficiency with which they are detected may differ. In contrast, the PSA bound to a2-M is probably engulfed in the oo-M structure, renOver the past several years, there has been tremendous interest in prostate-specific antigen (PSA) because it is usually present at higher than normal levels in the serum of prostate carcinoma patients and is therefore useful as a marker for diagnosing this disease and monitoring the therapy [1,2].…”
Section: Introductionmentioning
confidence: 99%